2013
DOI: 10.3111/13696998.2013.792824
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of subcutaneous interferon beta-1a 44mcg 3-times a week vs no treatment for patients with clinically isolated syndrome in Sweden

Abstract: The risk of conversion from CIS to MS was extrapolated from 2-year trial data. Treatment benefit was assumed to persist over the model duration, although long-term data to support this are unavailable. Cost and QoL data from MS patients were assumed applicable to CIS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 14 publications
0
27
1
Order By: Relevance
“…On the basis of title and abstract, 435 records were excluded and the remaining 17 records were included for full-text screening. A further eight articles were excluded at the full-text stage, with the reasons for exclusion provided in Appendix 6, leaving nine studies [254][255][256][257][258][259][260][261][262] that included a decision-analytic model, which were used to estimate the cost-effectiveness of DMTs for treating people with CIS.…”
Section: Methods For the Assessment Of Cost-effectiveness Studiesmentioning
confidence: 99%
“…On the basis of title and abstract, 435 records were excluded and the remaining 17 records were included for full-text screening. A further eight articles were excluded at the full-text stage, with the reasons for exclusion provided in Appendix 6, leaving nine studies [254][255][256][257][258][259][260][261][262] that included a decision-analytic model, which were used to estimate the cost-effectiveness of DMTs for treating people with CIS.…”
Section: Methods For the Assessment Of Cost-effectiveness Studiesmentioning
confidence: 99%
“…All studies concluded in favor of the sponsored DMD, their results conflicting depending on the sponsor in the studies on RRMS. Unsurprisingly, time horizons and discount rates were the most influential variables in sensitivity analyses in four of the six studies [10][11][12]15] with a long-term horizon.…”
Section: Economic Evaluations In the European Unionmentioning
confidence: 99%
“…Five studies were based on Markov models with a long-term horizon and two on 'decision trees' [12,16], only one of them with a short-term horizon [16]. All studies used virtual cohorts of patients, only three referring to samples of clinical trials to define the virtual cohorts [10,11,16]. Extrapolation of short-term efficacy to long-term time horizons was performed in all studies but one [16].…”
Section: Economic Evaluations In the European Unionmentioning
confidence: 99%
See 2 more Smart Citations